Ancient Turkic ritual fences on the burial ground Ulken Kakpak (Journal of history, 2022)
The article is devoted to the introduction into scientific circulation of information about the ritual monument of the ancient Turkic time, studied at the Ulken Kakpak burial ground, located in the north-eastern part of Zhetysu. In the course of the study, complex archaeological exploration and excavation works were carried out, in connection with the structural features of the monument, a widely used comparative typological method was used, and a technical and technological analysis of the fragments of ceramic dishes found was carried out. The analysis of ceramic tableware was carried out on the basis of binocular microscopy methods and was classified according to three main stages of the manufacture of ceramic tableware. The studied ritual fences represent a whole complex with burials randomly located in one burial ground. Despite the fact that only fragments of ceramic ware were found during the study of ritual fences, based on the design features of the fences and comparing them with those previously studied in neighboring regions, we can say that the monument dates back to the early Middle Ages. Of particular interest is the special treatment of the upper part of the stele, installed on the outside of the northern wall of fence no. 1. The ritual fence can be built by followers of ancient Turkic beliefs during the penetration of Islam into this region.During the archaeological excavations at the Ulken Kakpak burial ground, located in Zhetysu, which was the center of the Turkic khaganates, many sources were obtained for the study of early medieval ritual monuments. Among other things, materials were collected concerning the ritual beliefs and worldview of the ancient Turkic time. The monument is dated by the authors of the VIII–IX centuries.